Transforming Public Administration Inclusion Practices in Community-Based Social Policy in the Era of Technological Disruption - Sri Sulandari; Wahyu Ana Muliasari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines how inclusive public administration is implemented through community-based social policies amid technological disruption. Using a qualitative case study in Sanur Village, Denpasar, Bali, data were gathered from in-depth interviews with eight key informants, participatory observations, and policy document analysis. Findings show that technological disruption expands public service access and accelerates government–citizen interaction, yet also risks excluding vulnerable groups. Inclusion is effectively achieved when formal policies are supported by adaptive local community initiatives. The study contributes to the theory of inclusion in public administration and offers practical insights for developing participatory, adaptive, and responsive community-based social policies in the digital disruption era.